Antara Merdeka dan Dijajah: Problematika Kawula Desa Perdikan di Wilayah Eks Karesidenan Madiun, 1742-1962 - Qomar, Akhlis Syamsal; Pratama, Setya Yoga (Jurnal Sejarah Indonesia, 2024)
This research focuses on examining the social and economic aspects of perdikan villages, especially the problems of perdikan village people in the former Madiun Residency area. This research uses historical research methods with a social and economic approach. The relationship between kawula and priyayi in several perdikan villages in the former Madiun residency area has not resulted in significant conflict, although in practice the kwula are still charged with taxes and the obligation to work. Apart from the psychological factor of the kawula that they were bound by a relationship with the perdikan village gentry because they lived on their land, the working relationship was only between the kawula and the perdikan village gentry, not between the kawula and the Dutch East Indies colonial government.